Stereotactic body radiotherapy for benign spinal tumors: Meningiomas, schwannomas, and neurofibromas - Hwang, Lindsay (J Radiosurg SBRT, 2019)
Stereotactic body radiation therapy (SBRT) is a relatively new technology, and its use among patients with benign spinal tumors has limited prospective data. Similar to intracranial benign tumors treated successfully with SBRT, benign spinal tumors of the same histology can also develop, and SBRT may be an effective treatment alternative in inoperable or recurrent cases. Outcomes in patients with neurofibromatosis type 1, neurofibromatosis type 2, or schwannomatosis treated with SBRT have also been reported. Single institution reports have shown local control rates over 90% and improvement in clinical symptoms. The optimum dose and fractionation to maximize local control and minimize toxicity is unknown, with few incidences of radiation treatment-related toxicities. Given the location and benign nature of these tumors, careful management of dose to critical organs is essential. With continued follow-up, the optimum use of SBRT in patients with benign spinal tumors can be better defined.